Assessment of students’ knowledge regarding breast self-examination in Erbil City-Iraq - azez, Kareem; Sheren, nazar (Iraqi National Journal of Nursing Specialties, 2011)
Breast cancer is the most common cause of death among women worldwide (1) . Breast self-exam (BSE) is considered an important public health procedure; primary prevention should be given the highest priority in the fight against cancer. Cancer is considered the second leading cause of death in developed countries there was some 6.2 million cancer related deaths, accounƟng for 12% of all deaths globally (5).Patients perception toward this disease and preference concerning the types and aims of their treatment are vary they may loss hopes and become devastated and crippled or even dies earlier, if told about the diagnosis (13). The study aimed to assess knowledge of female students regarding BSE, and to find out relationship between sociodemographic variables and breast self-exam. One hundred of female students from, Medical technical institute in the first and second class were selected to participate in the study. The questionnaire was designed for data collection. The data were collection from January 1 st , 2010 to March 20th , 2010. The questionnaire it consists of two parts related to sociodemoraphic characteristics for study sample, and female student’s knowledge about breast self exam. The study revealed that female student’s knowledge about breast selfexam was reported poorly, and there were no significant differences among study sample about. The study revealed that female students’ knowledge about breast self-exam was reported poorly according to their age, marital status, and economic status. The study recommended to emphasizing to curriculum of Medical Technical Institute and should be included breast cancer knowledge and prevention, and Implementation of health education program for female students to raise breast cancer knowledge and awareness among female students